Effect of calcium from dairy and dietary supplements on faecal fat excretion: a meta-analysis of randomized controlled trials - Christensen, R; Lorenzen, J.K; Svith, C.R; Bartels, E.M; Melanson, E.L; Saris, W.H; Tremblay, A; Astrup, A (Obesity reviews, 2009)
Observational studies have found that dietary calcium intake is inversely related to body weight and body fat mass. One explanatory mechanism is that dietary calcium increases faecal fat excretion. To examine the effect of calcium from dietary supplements or dairy products on quantitative faecal fat excretion, we performed a systematic review with meta-analysis. We included randomized, controlled trials of calcium (supplements or dairy) in healthy subjects, where faecal fat excretion was measured. Meta-analyses used random-effects models with changes in faecal fat excreted expressed as standardized mean differences, as the studies assessed the same outcome but measured in different ways. An increased calcium intake resulted in increased excretion of faecal fat by a standardized mean difference of 0.99 (95% confidence intervals: 0.63-1.34; P < 0.0001; expected to correspond to ~2g day⁻¹) with moderate heterogeneity (I² = 49.5%) indicating some inconsistency in trial outcomes. However, the dairy trials showed homogeneous outcomes (I²=0%) indicating consistency among these trials. We estimated that increasing the dairy calcium intake by 1241 mg day⁻¹ resulted in an increase in faecal fat of 5.2 (1.6-8.8) g day⁻¹. In conclusion, dietary calcium has the potential to increase faecal fat excretion to an extent that could be relevant for prevention of weight (re-)gain. Long-term studies are required to establish its potential contribution.